Comparative Analysis of Musculoskeletal Disorder Between Female and Male Mechanical Pickers in Gambung Tea Plantation, West Java - Silvia Senjaya; Yayuk Yuliati; Dhia Al-Uyun; Kralawi Sita (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2022)
Previous research has shown that musculoskeletal disorders (MSDs) are one of the barriers for women to adopting tea-picking mechanization technology. Musculoskeletal disorders (MSDs) are defined as a group of injuries that affect the musculoskeletal system including nerves, tendons, muscles, and supporting structures. MSDs are also referred to as injuries due to overactivity or from using a device excessively. Some research results significantly show that gender greatly affects the level of risk of autonomic complaints and that women are more likely to show musculoskeletal symptoms than men. This study examines the comparison of musculoskeletal disorders due to the use of tea picking machines for male and female pickers.  Data collection on musculoskeletal disorders (MSDs) complaints was carried out using the Nordic Body Map instrument, in the form of an open questionnaire by interviewing mechanical tea pickers directly. From the data obtained, the average difference in scores for male mechanical tea pickers is 5.3 while the average difference in scores for female mechanical tea pickers is 9. This means that the average female mechanical tea pickers experience musculoskeletal complaints 70% more height than male mechanical tea pickers. MSDs complaints comparison between male and female tea pickers with NBM measurement is 5:9. In conclusion, female mechanical tea pickers suffer from MSDs almost twice as much as males. Considering that the majority of tea pickers are women, gender-responsive machine design interventions are needed.